Ann's story - International Livestock Research Institute (2012)
During the drought of 2009 many Kenyan pastoralists were forced to move with their livestock in search of grazing land. We met Ann and her family in the rangelands outside of Nairobi. This is her story of how the drought has affected her life. This photofilm was part of a duckrabbit training productions for ILRI in Nairobi in August 2010. The audio and production was led by ILRI's Muthoni Njiru, Tezira Lore and Julius Nyangaga (formerly with ILRI). The majority of the photos are by David White of duckrabbit).